1992
DOI: 10.1093/oxfordjournals.eurheartj.a060155
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of L-propionylcarnitine vs L-carnitine in improving walking capacity in patients with peripheral vascular disease: an acute, intravenous, double-blind, cross-over study

Abstract: The effects of L-propionylcarnitine on walking capacity were assessed in a group of patients with peripheral vascular disease. In 12 patients, 300 mg of L-propionylcarnitine, given intravenously as a single bolus did not affect walking capacity, while 600 mg increased both initial claudication distance from the placebo value of 179 +/- 114 to 245 +/- 129 m (P less than 0.05), and maximal walking distance from 245 +/- 124 to 349 +/- 155 m (P less than 0.05). Once the efficacious dose of L-propionylcarnitine was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 0 publications
0
35
0
5
Order By: Relevance
“…Examples include cardiac myopathies and peripheral arterial disease (Ferrari et al 1992), and improving the walking capacity in patients with peripheral vascular disease (Brevetti et al 1992). In animal models, l -carnitine and its derivatives have shown some bene® cial eOE ect such as protection against the development of vascular lesions in peripheral arterial insu ciency induced by intra-arterial injection of sodium laurate (Corsico et al 1993), the prevention of progression of atherosclerotic lesions (Spagnoli et al 1995) and age-dependent rise of plasma total cholesterol, triglycerides and uric acid of SHR (Rauchova!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include cardiac myopathies and peripheral arterial disease (Ferrari et al 1992), and improving the walking capacity in patients with peripheral vascular disease (Brevetti et al 1992). In animal models, l -carnitine and its derivatives have shown some bene® cial eOE ect such as protection against the development of vascular lesions in peripheral arterial insu ciency induced by intra-arterial injection of sodium laurate (Corsico et al 1993), the prevention of progression of atherosclerotic lesions (Spagnoli et al 1995) and age-dependent rise of plasma total cholesterol, triglycerides and uric acid of SHR (Rauchova!…”
Section: Discussionmentioning
confidence: 99%
“…Despite most published data on carnitine and its derivates being favourable, clinical trials have been relatively scanty and the mechanism by which the function during ischaemia is improved is not fully known. An unknown mechanism of action is implicated in improving the walking capacity in patients with peripheral vascular disease (Brevetti et al 1992) and alternative mechanisms, independent of the classical metabolic pathways, have been proposed to explain the bene® cial eOE ects of these compounds (Fritz et al 1993).…”
mentioning
confidence: 99%
“…A number of short-chain carnitine esters of LC have been proposed for pharmacological use. For example, propionyl-L-carnitine (PLC), which is produced by esterification of the hydroxyl group of LC and is an important component of the endogenous carnitine pool, has been evaluated for the treatment of peripheral arterial diseases and other cardiovascular disorders (Böhmer and Bremer, 1968;Bartels et al, 1992;Brevetti et al, 1992;Duprez et al, 2003).…”
mentioning
confidence: 99%
“…Furthermore, our results support prior observations of the potential efficacy of l-carnitine in clinical trials of PAD. [11][12][13][14][15] Initial studies by Brevetti where l-carnitine was administered by oral 18 and intravenous 19 routes showed that supplementation with l-carnitine improved exercise performance in patients with IC. In the past decade, two pivotal multicenter, doubleblinded, placebo-controlled RCTs have demonstrated the efficacy of extended carnitine therapy in PAD (delivered as propionyl-l-carnitine).…”
Section: Discussionmentioning
confidence: 99%